Diffusion Model Applied to Postfeeding Larval Dispersal in Blowflies (Diptera: Calliphoridae) - Bassanezi, R. C.; Leite, M. B F; Godoy, W. A C [UNESP]; Von Zuben, C. J.; Von Zuben, F. J.; Dos Reis, S. F. (FapUNIFESP (SciELO), 1997)
This paper presents a diffusion model of larval dispersal especifically designed to account for particular aspects of postfeeding larval dispersal from the food source in organisms such as blowflies. In these organisms the dispersal of immatures includes two groups of individuals, those that are actively migrating and those that have initiated the pupation process. The classical diffusion equation in one dimension was modified to incorporate a function which describes the burying of larvae to become pupae. The analytical solution of this equation predicts oscillatory and monotonic dispersal behaviors, which are observed in experimental populations of blowfly species.
Keywords: Blowflies; Chrysomya megacephala; Chrysomya putoria; Cochliomyia macellaria; Diffusion model; Larval dispersal; Calliphoridae; Diptera; Megacephala; Putoria